SUMBER DAYA MANUSIA, GOOD CORPORATE GOVERNANCE, DAN KINERJA PERUSAHAAN - Putri, I G A M Asri Dwija (PIRAMIDA; Vol 11 No 1 (2015): Jurnal PIRAMIDA, 2015)
This article aims to discuss the human resources, good corporate governance and corporate performance. Human resources in the accounting world often termed Human capital. Human capital for the company can be regarded as an intangible asset. Five principles of good corporate governance, namely transparency, accountability, responsibility, independence and fairness guide the running of the company to be able to improve the performance of the company. Human capital and good corporate governance is a factor that can affect the performance improvement company.
Keywords: human capital, good corporate governance, performance